2018
DOI: 10.5946/ce.2017.177
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Endoscopic Diagnosis for Mild Atrophic Gastritis Infected with Helicobacter pylori

Abstract: Background/AimsThis study examined the accuracy of endoscopic evaluation for determining the Helicobacter pylori infection status in patients with mild atrophy who might not exhibit characteristic endoscopic findings. MethodsForty endoscopists determined the H. pylori infection status of 50 randomly presented H. pylori-positive and H. pylori-negative cases on the basis of a list of established findings. ResultsThe median clinical endoscopy experience was 7 years (range, 1–35 years), including 22 board-certifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The vast majority of studies report a fair agreement between the endoscopic and histological diagnosis of gastritis, particularly in children and support the routine collection of biopsy samples during endoscopy in pediatric patients [20][21][22]. This high discrepancy might stem from the differences in the geographic distribution of H. pylori infection and not necessarily from the endoscopist's experience [23]. In contrast to other studies, the Cohen's k coefficient of 0.42 determined in our analysis indicates a good agreement between the two methods; this could be explained by the high prevalence of infection in our country.…”
Section: Discussionmentioning
confidence: 93%
“…The vast majority of studies report a fair agreement between the endoscopic and histological diagnosis of gastritis, particularly in children and support the routine collection of biopsy samples during endoscopy in pediatric patients [20][21][22]. This high discrepancy might stem from the differences in the geographic distribution of H. pylori infection and not necessarily from the endoscopist's experience [23]. In contrast to other studies, the Cohen's k coefficient of 0.42 determined in our analysis indicates a good agreement between the two methods; this could be explained by the high prevalence of infection in our country.…”
Section: Discussionmentioning
confidence: 93%
“…Okamura et al [15] reported that the accuracy of endoscopic diagnoses of H. pylori infections in patients with mild atrophic gastritis was approximately 67%. There was no significant difference in the accuracy rate between experienced endoscopists and trainees.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The summarized numerical data were expressed as medians with SDs and compared using Student t tests. Fleiss' κ was used to evaluate the inter-observer agreement [14,15]. A p value of < 0.05 in each analysis was considered statistically significant.…”
Section: Sample Sizementioning
confidence: 99%
“…At endoscopy, gastritis is described as any reddening or edema of the gastric mucosa, but neither of these endoscopic features is specific or exclusive to mucosal inflammation. A Japanese study on the accuracy of standard endoscopic imaging for the detection of H. pylori infection reported accuracy of 89% for nodularity and 77% for mucosal swelling [3].…”
Section: Introductionmentioning
confidence: 99%